Plasmodium falciparum Liver Stage Infection and Transition to Stable Blood Stage Infection in Liver-Humanized and Blood-Humanized FRGN KO Mice Enables Testing of Blood Stage Inhibitory Antibodies (Reticulocyte-Binding Protein Homolog 5) In Vivo - Foquet, Lander; Schafer, Carola; Minkah, Nana K.; Alanine, Daniel G. W.; Flannery, Erika L.; Steel, Ryan W. J.; Sack, Brandon K.; Camargo, Nelly; Fishbaugher, Matthew; Betz, Will; Nguyen, Thao; Billman, Zachary P.; et al. (Frontiers in Immunology, 2018)
Abstract The invention of liver-humanized mouse models has made it possible to directly study the pre-erythrocytic stages of Plasmodium falciparum. In contrast, the current models to directly study blood stage infection in vivo are extremely limited. Humanization of the mouse blood stream is achievable by frequent injections of human red blood cells (hRBCs) and is currently the only system with which to study human malaria blood stage infections in a small animal model. Infections have been primarily achieved by direct injection of P. falciparum-infected RBCs but as such, this modality of infection does not model the natural route of infection by mosquito bite and lacks the transition of parasites from liver stage infection to blood stage infection. Including these life cycle transition points in a small animal model is of relevance for testing therapeutic interventions. To this end, we used FRGN KO mice that were engrafted with human hepatocytes and performed a blood exchange under immune modulation to engraft the animals with more than 50 % hRBCs. These mice were infected by mosquito bite with sporozoite stages of a luciferase-expressing P. falciparum parasite, resulting in noninvasively measurable liver stage burden by in vivo bioluminescent imaging (IVIS) at days five to seven post-infection. Transition to blood stage infection was observed by IVIS from day 8 onward and then blood stage parasitemia increased with a kinetic similar to that observed in controlled human malaria infection. To assess the utility of this model, we tested if a monoclonal antibody targeting the erythrocyte invasion ligand RH5 (with known growth inhibitory activity in vitro) was capable of blocking blood stage infection in vivo when parasites emerge from the liver and found it highly effective. Together, these results show that a combined liver-humanized and blood-humanized FRGN KO mouse model infected with luciferase-expressing P. falciparum will be a useful tool to study P. falciparum pre-erythrocytic and erythrocytic stages and enables the testing of interventions that target either one or both stages of parasite infection.